Respuesta :
Option 2 is the correct option
Step-by-step explanation:
Step 1 :
Given expression : (x + 12)(x - 12)
We need to find the expression from the given options which matches the given expression
Step 2 :
The given expression is of the form (a+b)(a-b)
where a = x and b = 12 here
The product of this is given by formula
(a+b)(a-b) = (a² - b²)
Substituting the value of a and b in formula we get
(x + 12)(x - 12) = x² - 12² = x² - 144
Hence option 2 is the correct option from the given list.
Step 3 :
Answer :
Option 2 is the option which matches the given expression